2010
DOI: 10.1002/bmc.1352
|View full text |Cite
|
Sign up to set email alerts
|

Isothiocyanates as derivatization reagents for amines in liquid chromatography/electrospray ionization–tandem mass spectrometry

Abstract: The applicability of 3-pyridyl isothiocyanate, p-(dimethylamino)phenyl isothiocyanate and m-nitrophenyl isothiocyanate as the derivatization reagents for amines in high-performance liquid chromatography/electrospray ionization-tandem mass spectrometry (LC/ESI-MS/MS) was examined. The generated derivatives of amines with these reagents were favorably separated on the reversed-phase column and detected by ESI-MS/MS. The C-N bond of the generated thiourea structure was efficiently cleaved by collision-induced dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Their generated derivatives gave the intense product ions at m/z 137, m/z 179 and m/z 137, respectively (Fig. 4b; Santa, 2010).…”
Section: Derivatization Reagentsmentioning
confidence: 99%
“…Their generated derivatives gave the intense product ions at m/z 137, m/z 179 and m/z 137, respectively (Fig. 4b; Santa, 2010).…”
Section: Derivatization Reagentsmentioning
confidence: 99%
“…In the previous paper, we have reported that the compounds having an isothiocyanate group were suitable as the derivatization reagents for amines in LC/ESI‐MS/MS. The generated compounds, having thiourea structure, efficiently produced a particular fragment ion by CID (Santa, 2010). It was also reported that the compounds having thiourea structure often gave the clear product ion spectra (Claeson et al ., 2004; Ji and Morris, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…These include p ‐ N , N , N ‐trimethylaminoaninyl‐ N '‐hydroxysuccinimidyl carbomate iodide (TAHS) (Shimbo et al ., 2009a), 3‐aminopyridyl‐N‐hydroxysuccinimidyl carbamate (APDS) (Shimbo et al ., 2009b) for amines, 2‐hydrazino‐1‐methylpyridine (HMP) (Higashi et al ., 2005a), 4‐[2‐( N , N ‐dimethylamino)ethylaminosulfonyl]‐7‐ N ‐methylhydrazino‐2,1,3‐benzoxadiazole (DAABD‐MHz) (Santa et al ., 2008) for ketones, isonicotinoyl azide (NA) (Higashi et al ., 2007) for alcohols, dansyl chloride for phenols and 4‐[2‐( N , N ‐dimethylamino)ethylaminosulfonyl]‐7‐(2‐aminoethylamino)‐2,1,3‐benzoxadiazole (DAABD‐AE) for carboxylic acids (Al‐Dirbashi et al ., 2008; Santa et al, 2007b; Tsukamoto et al ., 2005). In the previous paper, we reported that the compounds with a thiourea structure, generated by the reaction of amines with isothiocyanates, afforded a particular product ion efficiently by CID and were suitable for the MS/MS detection (Santa, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The values of LLOD using these methods were 50-500 amol/injection. Several HPLC-MS/MS reagents with pyridinyl moieties, 3-pyridyl isothiocyanate (Py-NCS) and 3-aminopyridyl-N-hydroxysuccimidyl carbamate (APDS), have also been reported [18,35]. These reagents are also used for highly sensitive determination of amino compounds by HPLC-MS/MS.…”
Section: Design and Synthesis Of A Novel Fl/ms/ms Reagent With A 6-momentioning
confidence: 97%